(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Egypt is one of the most populous countries in the Middle East and Africa. Evidence from developing countries revealed that increasing family planning use is associated with substantial declines in fertility and population growth. The objective of this study was to assess the impact of implementing a multisectoral intervention model on the family planning utilization at the Primary Health Care (PHC) level in a priority district, Fayoum governorate, Egypt. Methods: A quasi-experimental design was conducted from July 2016 to September 2016. The model targeted 10 PHC units out of 23 at Tamia district, with two types of interventions; health sector and non-health sector related interventions carried out in the intervention units and their catchment areas. The family planning utilization of the intervention units (n=10) was compared to the control units (n=13). Additionally, the overall family planning utilization at the district level was measured. Results: Following the implementation of the interventions, the overall family planning utilization at the district level showed a significant increase in mean ± Standard Error of the Mean (SEM) of new family planning clients (44.4±11.0vs. 63.3±13.8; P= 0.006) recording 43% change. The mean ± SEM of intrauterine devices dispensed from the intervention units significantly increased by 391% (3.5±1.0 vs. 17.2±3.3; P=0.002). Findings from the control units didn’t reveal significant increase regarding the dispense of any family planning method. Conclusion: Mobilizing and optimizing resources use, empowering district authorities and strengthening collaboration across sectors were key drivers of the success of this model in scaling up family planning services utilization.